A bionic manipulator based on multi-sensor data fusion. Issue 192 (2nd September 2018) - Qian, Chenghui; Li, Xiang; Zhu, Jianfeng; Liu, Tao; Li, Ruilin; Li, Bingyang; Hu, Mengyuan; Xin, Yi; Xu, Yang
Abstract: Most of manipulators possesses have drawbacks like only moving in fixed mode and intensity, cannot achieve self-adjusting and soft grabbing, etc. Herein, a four degree of freedom bionic manipulator based on multi-sensor data fusion technology is designed. The manipulator gathers electrical signal using piezoelectric sensor based on polyvinylidene fluoride (PVDF) film. A conditioning circuit is used to process signal. The manipulator is controlled to adjust grasping way according to orders that is obtained by data fusion. The manipulator achieves bionic function, which can grasp irregular and fragile object, also, it can bounce off automatically when approaching objects with high temperature.